2018
DOI: 10.1017/s0033291718000867
|View full text |Cite
|
Sign up to set email alerts
|

A comparative network analysis of eating disorder psychopathology and co-occurring depression and anxiety symptoms before and after treatment

Abstract: Findings suggest that symptoms related to shape and weight concerns and guilt are central ED symptoms, while physical symptoms, self-esteem, and feeling overwhelmed are links that may underlie comorbidities in EDs. Results provided some support for the validity of network approaches, in that admission networks conveyed prognostic information. However, the lack of correspondence between symptom reduction and change in network strength indicates that future research is needed to examine network dynamics in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 51 publications
11
106
0
Order By: Relevance
“…The present findings are in line with previous studies which identified anxiety and depressive symptoms as well as interpersonal difficulties and ineffectiveness as the most central nodes in adult outpatients with mixed ED diagnoses (Solmi et al, ) and in an adult outpatient AN sample (Solmi et al, ). Another recent work also proved that negative affect symptoms, such as low self‐esteem, concentration difficulties, feeling overwhelmed and nervousness as well as shape and weight related concerns are central nodes in a network comprising a hospitalized adult ED population before and after treatment (Smith et al, ). Our study is the first to be carried out in an adolescent population with AN in the early phase of the illness (illness duration <3 years) whereas the above cited studies have been conducted in older populations with a longer illness duration.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The present findings are in line with previous studies which identified anxiety and depressive symptoms as well as interpersonal difficulties and ineffectiveness as the most central nodes in adult outpatients with mixed ED diagnoses (Solmi et al, ) and in an adult outpatient AN sample (Solmi et al, ). Another recent work also proved that negative affect symptoms, such as low self‐esteem, concentration difficulties, feeling overwhelmed and nervousness as well as shape and weight related concerns are central nodes in a network comprising a hospitalized adult ED population before and after treatment (Smith et al, ). Our study is the first to be carried out in an adolescent population with AN in the early phase of the illness (illness duration <3 years) whereas the above cited studies have been conducted in older populations with a longer illness duration.…”
Section: Discussionmentioning
confidence: 98%
“…One of these found that physical sensations were the bridge symptoms between bulimia nervosa and anxiety and depression (Levinson et al, ). Two studies demonstrated the connection between self‐esteem and shape and weight problems (Elliott et al, ; Smith et al, ). The remaining two works identified symptoms connecting social anxiety or PTSD symptoms and ED symptoms, respectively (Levinson, Brosof, et al, ; Vanzhula et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been partially born out in the data; studies have shown that depressed patients have increased connectivity among depression symptoms compared to healthy controls [3][4][5] and the same is true for several other disorder groups [6][7][8][9]. Moreover, participants who go on to have persistent depression have more strongly connected networks at baseline than those who ultimately achieve remission [10,11] and the same appears to be true for eating disorder patients who undergo treatment [12]. Approaching a change in a system's state, e.g.…”
Section: Introductionmentioning
confidence: 96%